A PROFILE STUDY OF DROWNING IN THE DECEASED BROUGHT TO THE MORTUARY OF CIVIL HOSPITAL, AHMEDABAD (Journal of Forensic Medicine & Toxicology, 2016)
Drowning is a form of asphyxial death in which the access of air to the lungs is prevented by the submersion of the body in the water or other fluid media. Drowning is a common method of committing suicide as it causes immediate and painless death. This study was undertaken by Department of Forensic Medicine, B. J. Medical College, Civil Hospital, Ahmedabad to know epidemiological aspects, pattern and other significant features of death due to drowning in Ahmedabad district. In this study, it is observed that maximum cases were found in the month from May to September which concludes that drowning cases occur mostly in summer and monsoon seasons. Incidence was much more common in males and the age group of 21-30 years was prone to drowning cases. It was also found that suicidal drowning was more common than accidental drowning. Incidence was slightly higher in urban area than in rural areas.
Keywords: Drowning; Asphyxia; Diatoms; Manner of death